Antioxidant Activity, Ascorbic Acid, and Beta Carotene of Sumatran Red Tampoi (Baccaurea costulata) and Rambai (Baccaurea motleyana) Fruits - Pardede, Erika; Julianti, Elisa; Siahaan, Ferlist Rio; Harefa, Claudia Virani (Universitas Panji Sakti, 2024)
This study evaluated the antioxidant activity, ascorbic acid, and beta-carotene levels in two underutilized species of Sumatran Baccaurea Lour. The fruit of red tampoi or Baccaurea costulata (Miq.) Műll. Arg is orange, while rambai or Baccaurea motleyana (Műll. Arg) Műll. Arg has a pale-yellow color with an “a” value of 29.22±0.51 and 2.67±0.58, respectively, measured with a hand chromameter. The half-maximum inhibitory concentration (IC50) of the free radical scavenging activities of both fruits was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging method. The IC50 of B. costulata (51.63±3.42 µg/g) indicated that its fruit juice has a strong antioxidant property, while B. motleyana (76.95±1.28 µg/g) has a moderately antioxidant characteristic. A high antioxidant activity of B. costulata was followed by a high amount of ascorbic acid (55.86±1.73 mg/100g) and beta carotene (150.77±2.16 μg/g), in comparison to those of B. motleyana, which has a lower amount of ascorbic acid (37.30±2.34 mg/100g) and beta carotene (25.36±1.37 μg/g). It was also found that there was a moderate correlation between scavenging capacities (expressed as the reciprocal of the calculated IC50 value), a strong positive correlation with beta-carotene (r2 = 0.90), and a moderately positive correlation with ascorbic acid (r2 = 0.77). It can be concluded that both Baccaurea fruits are nutritious foods due to their high ascorbic acid and beta-carotene content, and they also possess high antioxidant properties. Both ascorbic acid and beta-carotene contributed significantly to the antioxidant activity.